(3OhQ GddLfI GdOhdjI ddUdjH GdCMeQ aj JWHjb GdbGfhf GdOhdj GdEfSGfj (B/ s - (3TQja CMeO eOMJ YJde s; (3eMeO SGeM YeQhs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3Je JcQjS gPg GdCWQhMI(B: (3GdJj JYJHQ ef ChGFd GdeDdaGJ HGddZI GdYQHjI(B: (3dOQGSI eJNUUI ddLfI GdOhdjI ddUdjH GdCMeQ(B: (3Ydi SHjd GdGSJfKGQ h GdJNUjU(B. (3hgj JJfGhd HjGf ghjJgG cefXeI EfSGfjI eMGjOI(B: (3JYed Ydi MeGjI h eSGYOI GdVMGjG ai Ref GdefGRYGJ GdeSdMI(B. (3h aj gPG GdEWGQ(B: (3cGf dRGeG Ydi GddLfI GdOhdjI ddUdjH GdCMeQ Cf jchf dgG efgL Yed aQjO gh efgL GdSQjI(B: (3GdPi jJjM dgG GdJaGhV eY GdCWQGa GdeJfGRYI Ohf GddLhA Edi GdYdf(B: (3ddMjdhdI Ohf efY hUhdgG ddVMGjG Ef gj CUHMJ NUeG eY CWQGa GdfRGYs
(3jTJed Ydi edGMb(B: (3UaMI (B409-467s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi, (B2010s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B468-500s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdOhdjs; (3EJaGbjGJ Ljfjas; (3GdbGfhf GdOhdi GdEfSGfis; (3GddLfI GdOhdjI ddUdjH GdCMeQs; (3GdGSGS GdbGfhfi dYed ddLfI GdUdjH GdGMeQ s; (3GfJgGc GMcGe GdbGfhf GdOhdi GdGfSGfi s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs